Reconsidering the price-income relationship across countries - Eiji Fujii (Center for Economic Studies and ifo Institute (CESifo), 2013)
This study reconsiders the well-known cross-country positive association between prices and income by focusing on heterogeneity between the inter-developed-country and inter-developing-country relationships. Empirical results reveal not only that developed and developing countries differ in magnitude of the income effect on prices, but also that they exhibit the positive price-income association for different reasons. Specifically, we find only for the inter-developed-country case that the positive price-income association is attributable, at least partly, to the Balassa-Samuelson productivity differential effect. The idiosyncrasy of the inter-developing-country relationship is not dissolved by controlling for the effects of a variety of real and financial variables.
Keywords: F41; F31; E01; 330; Balassa-Samuelson effect; non-traded goods; purchasing power parity; Penn effect; price-income relationship; productivity differential; real exchange rate